Contrasting effects of acute and chronic treatment with imipramine and fluoxetine on inhibitory avoidance and escape responses in mice exposed to the elevated T-maze - Gomes, Karina Santos [UNESP]; de Carvalho-Netto, Eduardo Ferreira; Da Silva Monte, Katia Cristina [UNESP]; Acco, Bruno [UNESP]; de Campos Nogueira, Paulo Jose [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The elevated T-maze (ETM) is an animal model of anxiety-like behavior that assesses two different defensive behavioral tasks in the same animal-acquisition of inhibitory avoidance and latency to escape from an open and elevated arm. In rats, cute and chronic treatments with anxiolytic-like drugs impair avoidance acquisition while only chronic administration of panicolytic-like drugs impairs open arm withdrawal. To date, only the acute effects of anxiolytic/anxiogenic or panicolytic/panicogenic drugs have been tested in the mouse ETM and the results have partially corroborated those found in the rat ETM. This study investigated the effects of acute (a single intraperitoneal injection 30 min before testing) and chronic (daily i.p. injections for 15 consecutive days) treatment with imipramine or fluoxetine, non-selective and selective serotonin reuptake inhibitors, respectively, on inhibitory avoidance and escape tasks in the mouse ETM. Neither acute nor chronic treatment with imipramine (0, 1, 5 or 10 mg/kg, i.p.) significantly changed the behavioral profile of mice in the two ETM tasks. Interestingly, while acute fluoxetine (0, 5, 10, 20 or 40 mg/kg, i.p.) facilitated inhibitory avoidance and impaired escape latency, chronic treatment (0, 5, 20 or 40 mg/kg, i.p.) with this selective serotonin reuptake inhibitor (SSRI) produced an opposite effect, i.e., it impaired inhibitory avoidance acquisition and facilitated open arm withdrawal. Importantly, acute or chronic treatment with imipramine (except at the highest dose that increased locomotion when given acutely) or fluoxetine failed to alter general locomotor activity in mice as assessed in an ETM in which all arms were enclosed by lateral walls (eETM). These results suggest that inhibitory avoidance acquisition is a useful task for the evaluation of acute and chronic effects of SSRI treatment on anxiety in mice. However, as open arm latency was actually increased and reduced by acute and chronic fluoxetine, respectively, this does not seem to be a useful measure of escape from a proximal threat in this species. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Antidepressants; Imipramine; Fluoxetine; Acute and chronic treatment; Elevated T-maze; Inhibitory avoidance; Escape; Mice